TINJAUAN PENGENDALIAN KAS DAN REKONSILIASI BANK PADA PT. DATA ENERGY INFOMEDIA - Madeleine Ibrena br. Ginting (2020)
In carrying out business activities, every company requires control, one of which is cash control. This cash control is applied to protect cash, guarantee the accuracy of accounting records, and achieve accurate and relevant financial statement records. PT. Data Energy Infomedia applies control over cash receipts and disbursements. Implementation of cash receipts and disbursements controls by determining cash receipts and disbursements procedures, separation of responsibilities, and making vouchers. PT. Energy Data Infomedia also conducts bank reconciliations to help control cash. The Implementation of Field Work Practices aims to find out cash control and bank reconciliation conducted by PT. Infomedia Energy Data. Activities undertaken during the Field Work Practice are comparing and matching the recording of cash in the company with the recording of cash in the Bank, and reconciling banks with the help of Zahir Accounting. The benefits obtained from the Field Work Practice are knowing cash control and bank reconciliation of PT. Data Energy Infomedia, applies knowledge learned during lectures and increasingly understands reconciliation.